Businessing around comprehensive schooling - Seppänen Piia; Kiesi Iida; Lempinen Sonia; Nivanaho Nina (Springer, 2025)
The idea of education as a commodity, particularly as a field of export, has gradually taken hold in Finland creating a base for government collaboration with edu-business. In that logic comprehensive schooling for citizens in a small nation like Finland is positioned as a tool for a platform economy and to make profit within a sector of welfare society that has traditionally been considered separate from business-making forces. In this chapter after briefly describing the commercial actors in comprehensive schooling in Finland, we aim to understand how businessing around comprehensive schooling works in Finland based on interviews with different types of actors who aim to create this industry. We distinguish the rationalities, logics and modes of operation of edu-business. The rationale behind private actors’ involvement in comprehensive schooling in Finland rests on their claimed ability to create “innovations” that schools themselves cannot make, mainly related to the use of technology. Possible negative side effects are not discussed. Edu-preneurs emphasise “evidence based” activities done outside the academic community, nevertheless they call this research. Industry-making in education is conducted via networks facilitating various edu-business related activities by connecting interests and actors. We conclude that society needs to be wary of multiple lines of products and policy pressures by global edu-business creating new policies like auditing and quality assurance policies to guide and consult education policy-makers. Overall developments in businessing around comprehensive schooling raise questions about democracy and schooling as public service in a small nation like Finland.
Finland’s Famous Education System : Unvarnished Insights into Finnish Schooling